AN ECONOMIC STUDY TO MEASURE INFLUENCE OF THE MAIN VARIABLES IN RURAL POVERTY IN IRAQ DURING 1990 – 2019 - Al- Shipway, A. R. H.; Al- Wasity, R. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The research aims to measure influences of the main variables in rural poverty in Iraq during 1990 – 2019, so it used descriptive and qualitative methods to show the subject. The research reaches throw results of unit root test that all the variables were un stable in the level, but all of them were stabled after first difference. The research proved it`s hypothesis that all structural changes can lead to reduce the rural poverty in Iraq, the study explained positive relationship among the dependent variable ( per capita of national income) and independent variables ( rural population, agricultural labor, planted area of crops and the using technology), where increase by 1 % in each of the independent variables lead to increase in share of national income by ( 1.02, 3.6, 0.19,0.55) % respectively, this study showed there are decreasing in ratio of agri. product in GDP during the study period between % 20.4 .4 1995 and % 2.4 in 2018 and that indicated dependency of Iraq in crude oil and don’t have care with agricultural sector. The research recommends to planning of development strategy in Iraq`s countryside to reduce rural poverty and support the agri. Sector by modern technology.